How the Number of Players and Floaters’ Positioning Changes the Offensive Performance during Futsal Small-Sided and Conditioned Games - Travassos, Bruno (2021)
This study aims to analyse the effects of floater positioning within futsal Gk + 3vs3 + Gk and Gk + 2vs2 + Gk small-sided and conditioned games (SSCG) on youth offensive performance on an action per minute per player basis. Three experimental conditions were carried out through the manipulation of floater positioning: floaters off (FO), final line floaters (FLF) and lateral floaters (LF). Thirty male futsal players (U19 age category) participated in the study and played once within each situation in a random order on different days. Offensive performance based on “action per minute per player” was analysed through indirect and external systematic observation. Results showed significant differences between both SSCGs (2vs2 and 3vs3). Specifically, according to the game principles analysed, 3vs3 is associated with higher values of passing and dribbling action to progress towards the goal without beating a defensive line (moderate to large effect size), while 2vs2 is associated with higher values of passing and dribbling actions that beating a defensive line (moderate to very large effect size). In addition, 2vs2 is associated with dribbling and shooting actions to shoot at goal with the lowest level of opposition (moderate effect size). Indeed, whilst the 2vs2 game format seems to promote more 1vs1 situations, the 3vs3 game format encourages more ball possession and collective tactical behaviours. Thus, training tasks intended to improve dribbling and shooting actions should use a smaller number of players whereas tasks intended to improve passing actions for ball possession should include a higher number of players with or without floaters. It seems that the number of players can influence the tactical behaviour of the team. These findings should be considered for the design of futsal training tasks, according to the main objective of the training session. For example, if the coach aims to promote the number of dribbles and shots within a SSCG, 2vs2 SSCG situations should be prioritised.